(untitled) (Journal of Pharmaceutical Negative Results, 2022)
TNF-α is a multifunctional cytokine that regulates cell proliferation and differentiation, as well as immunological and host defense responses to infection. It also induces angiogenesis, modulates tissue remodeling, and controls apoptosis.TNF-α is a pleiotropic, pro-inflammatory cytokine that has the potential to be both pro-tumorigenic and anti-tumorigenic. TNF-α can be cytotoxic to tumour cells, slowing tumour progression or causing necrosis, and it can also enhance angiogenesis, proliferation, migration, and survival of tumour cells in oral cancer cells. Several research studies clearly imply that TNF-α and its soluble receptors could be effective in detecting, staging, and predicting prognosis in a variety of malignancies, including oral tumours. Well in many studies were conducted to detect the actual response of TNF- α, but lack of knowledge in understanding the true response of TNF-α towards oral precancer and oral cancer